PENERAPAN ISAK 35 TAHUN 2019 SERTA RELEVANSINYA DENGAN PSAK 69 AGRIKULTUR ATAS ASET BIOLOGIS TERHADAP PENYAJIAN LAPORAN KEUANGAN KELOMPOK TANI (STUDI KASUS PADA KELOMPOK WANITA TANI MAWAR KOTA KEDIRI) - Sagita, Monika Eli; Ratih, Nur Rahmanti; Suaidah, Imarotus (Jurnal Ilmiah Cendekia Akuntansi, 2024)
This study discusses the application of ISAK 35 on the presentation of the financial statements of nonlaba entities and its relationship with the application of PSAK 69 agriculture in the form of plants in the category of consumable biological assets (CBA), namely hydroponic melons. The purpose of the study was to determine the application of PSAK 69 Agriculture to assess biological assets owned by KWT Mawar and its presentation in the financial statements in accordance with ISAK 35 for nonlaba entities. The location of the study was conducted on the Mawar Women Farmers Group (KWT)in the area of Kampung Tani, Kleco, Jamsaren, Kediri. This type of research is descriptive quantitative with primary data sources. Data collection techniques used are interviews and direct documentation. Analytical techniques used are the collection, grouping, and analysis of data and conclude the results of research. The results showed that there has been no application of ISAK 35 for the preparation of financial statements because the entity only presents cash mutations, and there has been no application of PSAK 69 Agriculture on biological assets of KWT Mawar due to the lack of knowledge of the board in the field of accounting. All costs for the production of agricultural products are considered expenses. Non-presentation of financial statements causes the surplus received can not be clearly known. The holding of accounting training is needed as the first step for KWT Mawar to prepare an accountability report on its business activities.